COMPARATIVE ANALYSIS OF THE MINERAL COMPOSITION OF BENTONITE FROM CHERKASSY BENTONITIC AREA - Andreeva, O.; Shunko, V.; Grechanovska, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article discusses mineral composition of bentonites from the Cherkassy bentonitic area. The purpose of this work is to establish possible homogeneous and consistent nature of mineral composition of bentonites found throughout the area. Bentonites of this area is stratigraphically related to the Boyarska suite of Miocene, which sediments are widely distributed here. Sediments of Dashukivka field of the Cherkassy deposit and those sampled from the drill-hole 8504 are considered to be a stratotype of Boyarska suite. The mineral composition of bentonites collected in open pit of Dashukivka field are compared with that of early studied bentonites sampled from the drill-hole 8504. It was established that the mineral composition of bentonites is rather homogeneous, but there are some differences between samples. The single particles of montmorillonites (drill-hole 8504) are studied with using electron-probe analysis to determine homogeneity of chemical composition of clay sediments with using electron-probe analysis. By the results of point analyses chemical composition of montmorillonite is established to be homogeneous. The results of comparative studies of clay minerals testifies for very homogeneous nature of mineral composition of the Boyarska suite sediments. This fact gives opportunities to increase reserves of bentonites and palygorskites of the Cherkassy deposit.